2005
DOI: 10.1523/jneurosci.5045-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Promotes Rapid, Arrestin-Dependent Endocytosis of μ-Opioid Receptors in Striatal Neurons

Abstract: Morphine activates -opioid receptors (MORs) without promoting their rapid endocytosis in a number of cell types. A previous study suggested that morphine can drive rapid redistribution of MORs in the nucleus accumbens, but it was not possible in this in vivo study to identify a specific membrane trafficking pathway affected by morphine, to exclude possible indirect actions of morphine via opiateregulated neural circuitry, or to define the mechanism of this morphine-dependent regulation. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
121
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 45 publications
(60 reference statements)
7
121
0
Order By: Relevance
“…Many cell culture studies have manipulated kinase or ␤-arrestin expression to alter morphine-induced MOR trafficking. In neurons, Haberstock-Debic et al (44,45) showed that morphine-induced MOR trafficking differs between neurons and even within different regions of the same neuron. MOR trafficking was observed in the dendrites of nucleus accumbens neurons but not in the soma of the same neurons (45).…”
Section: Discussionmentioning
confidence: 99%
“…Many cell culture studies have manipulated kinase or ␤-arrestin expression to alter morphine-induced MOR trafficking. In neurons, Haberstock-Debic et al (44,45) showed that morphine-induced MOR trafficking differs between neurons and even within different regions of the same neuron. MOR trafficking was observed in the dendrites of nucleus accumbens neurons but not in the soma of the same neurons (45).…”
Section: Discussionmentioning
confidence: 99%
“…Morphine-stimulated MORs have been shown, with few exceptions (41,42), to elude internalization (43). It has been suggested that this aberrant trafficking of MORs results in prolonged activation of the MORs, leading to compensatory changes that result in tolerance to morphine.…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent studies provided evidence that desensitization and endocytosis of MOR occurred with morphine treatment (17,18). Activation of ERK1/2 by the mu opioid agonist DAMGO has been demonstrated in MOR-transfected cells and in neurons from morphine-treated mice (8,9).…”
Section: Discussionmentioning
confidence: 99%